The Translation of Address Terms in Showing Politeness from Chinese into English - Yu, Chunli; Mansor, Nor Shahila; Lay Hoon Ang; Sharon Sharmini (2021)
The proper translation of address terms plays a decisive role in the quality of translation practices. This paper explores the translation of Chinese address terms into English in showing politeness through a comparative analysis of the Chinese version Hong Lou Meng and its two famous English versions. It compares polite address terms in the two English versions A Dream of Red Mansions by Yang Hsien-yi & Gladys Yang, and The Story of The Stone by David Hawkes & John Minford respectively. The data for the study were sampled and collected from the three classic works. Hong Lou Meng is one of the four Chinese literary classics, which reflected the usage of Chinese address terms in an effective way. This study employs a descriptive qualitative research method. The analysis of address terms followed the framework of five politeness maxims in Chinese culture by Gu Yueguo (1992) based on the origin of Chinese culture. The findings suggest that address terms on politeness mostly reflected in “Selfdenigration Maxim” and “Address Maxim”, while “Agreement Maxim” and “Maxim of Virtue” are usually displayed through a series of conversations and actions. The two main aspects, self-abasing terms, and honorifics, of polite address terms discussed in many prior studies are included in the self-denigration maxim. In addition, in some cases, some politeness is lost during the Chinese-English translation of address terms for the culture differences. The translators are suggested to probe into the implied meaning of the polite address terms under the suitable context instead of transferring the literal meaning directly in most cases. These findings not only offer some empirical data on polite address terms, but also contribute to the translation studies. Furthermore, this study will offer some implications on the further construction of the politeness principles on address terms